Optimization of Polysaccharide Extraction Process from Rosa rugosa Residue and Analysis of Its Antioxidant Activity in Vitro - Tingyang ZHANG; Ling ZHANG; Yuqin JIANG; Yang LIU; Xinhui WANG; Xinxin ZHAO; Baohe MIAO (Shipin gongye ke-ji)
Rose flower residue, a major by-product of rose essential oil extraction, was used as the raw material in this study. The extraction process of polysaccharides from rose flower residue was optimized using single factor experiments combined with the Box-Behnken response surface method, with ultrasonic assistance and a composite enzyme treatment of cellulase and pectinase. The in vitro antioxidant activity of the polysaccharides was also investigated. Results showed that under the conditions of a material-to-liquid ratio of 1:15, a composite enzyme addition (cellulase to pectinase at a 1:1 ratio) of 1.9%, an enzymatic hydrolysis temperature of 47 ℃, and a duration of 84.5 min, the yield of polysaccharides from rose flower residue was 4.308%±0.03%. In vitro antioxidant tests showed that the rose flower residue polysaccharides had strong overall antioxidant capacity. At a polysaccharide solution concentration of 5 mg/mL, the FRAP value was 0.30, with strong scavenging abilities against DPPH· and ABTS+·, with scavenging rates of 98.93% and 92.19%, respectively. A weaker scavenging ability against O2−·, with a scavenging rate of 24.93%. Meanwhile, the IC50 value of DPPH·, ABTS+·, O2−· respective clearance capacity was 0.357, 0.608, and 64.206 mg/mL. This research provides a theoretical basis for the recycling and reuse of rose flower residue.